قواعد التفاضل في برامج العمل الخيري - الحبجر، عبدالله بن حسن محمد (جامعة الأزهر - کلية الدراسات الإسلامية والعربية للبنات بالإسكندرية, 2018)
قواعد التفاضل في برامج العمل الخيري يتناول هذا البحث قواعد التفاضل في برامج العمل الخيري، من حيث التعريف والأسباب، وأهم المقاصد وقد اشتمل البحث على: تمهيد: تناول تعريفي التفاضل والعمل الخيري، وحكمة التشريع في تنوع الأعمال الصالحة، وأسباب التفاضل بين الأعمال الصالحة، ومقاصد التفاضل بينها. المبحث الأول: قواعد عامة وتطبيقات في التفاضل بين الأعمال الصالحة. المبحث الثاني: قواعد وتطبيقات التفاضل في برامج العمل الخيري وفيه ثلاثة مطالب: المطلب الأول: قواعد التفاضل المتعلقة بالنية. المطلب الثاني: قواعد التفاضل المتعلقة بمتابعة النبي - صلى الله عليه وسلم. المطلب الثالث: قواعد وتطبيقات عامة للتفاضل في برامج العمل الخيري. وقد خلص البحث إلى أن أسباب التفاضل بين الأعمال الصالحة عموما، والخيرية خصوصا تعود إلي جلب المصلحة والمنفعة، ودفع المفسدة والمضرة، كما ترجع إلى الكيفية، والكمية، والحكم، والثمرة، والمشقة، والزمان، والمكان، وأن أهم مقاصد معرفة التفاضل بين الأعمال الصالحة هي تحري العمل الصالح الأفضل والأقرب إلى مرضاة الله تعالى، وثمة هناك قواعد عامة للتفاضل بين الأعمال الصالحة، وقواعد للتفاضل في برامج العمل الخيري، ولها تطبيقاتها.
Principles of Differentiation in Charitable work Programs This research addresses the principles of differentiation in charitable work programs in terms of definition, causes and the most important purposes. The research has incorporated the following: Introduction: which addresses the definition of both differentiation and charitable works. It also investigates the value of legislation in diversification of good deeds and the reasons and purposes of differentiation between them. The first topic: addresses general principles and applications in the differentiation between good deeds. The second topic: investigates principles and applications of differentiation in the charitable work programs. Further, this topic has three requirements: The first requirement: principles of differentiation related to intention. The second requirement: principles of differentiation related to the following-up of the Prophet peace be upon him. The third topic: General principles and applications for differentiation in charitable work programs. The research has concluded that the reasons for the differentiation between good deeds in general and charitable ones in particular are due to the interest and benefit, avoiding corruption and harmfulness, as well as the manner, quantity, the judgment, the advantage, the hardship, the time and the place. It has also founded that the most important purpose of differentiation in good deeds is to satisfy Allah Almighty. Moreover, there are general principles for the differentiation between good deeds, and others for differentiation in charitable work programs which have their own applications.
Keywords: التفاضل -- العمل الخيري -- الأعمال الصالحة